2011
DOI: 10.1128/cvi.05013-11
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Interleukin-2/Gamma Interferon Ratios in Mycobacterium tuberculosis-Specific T-Cell Signatures

Abstract: The simultaneous determination of interleukin-2 (IL-2) and gamma interferon (IFN-␥) in Quanti-FERON-TB test plasma supernatants permitted the detection of shifts in Mycobacterium tuberculosis-specific T-cell signatures. A subset of the 84 subjects tested revealed a significantly elevated IL-2/IFN-␥ ratio, which may be a marker for the successful elimination of M. tuberculosis infection.In countries with low tuberculosis (TB) incidence rates, such as Switzerland, targeted testing for latent Mycobacterium tuberc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 11 publications
(17 reference statements)
2
24
0
Order By: Relevance
“…Eleven out of the 16 publications [9,[17][18][19][20][21][22][23][24][25][26] dealing with IL-2 as a biomarker for the diagnosis of active and latent tuberculosis were considered to be eligible for inclusion in the qualitative analysis. For meta-analysis among these publications, six studies [4,8,10,20,27,28] were excluded because IFN-γ was detected only in patients with active tuberculosis [8], it was done in patients during and after their anti-tuberculosis treatment [10], the cytometric detection of IFN-γ-/IL-2-secreting cells was used [4,28], or they contained no detailed data [27].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eleven out of the 16 publications [9,[17][18][19][20][21][22][23][24][25][26] dealing with IL-2 as a biomarker for the diagnosis of active and latent tuberculosis were considered to be eligible for inclusion in the qualitative analysis. For meta-analysis among these publications, six studies [4,8,10,20,27,28] were excluded because IFN-γ was detected only in patients with active tuberculosis [8], it was done in patients during and after their anti-tuberculosis treatment [10], the cytometric detection of IFN-γ-/IL-2-secreting cells was used [4,28], or they contained no detailed data [27].…”
Section: Resultsmentioning
confidence: 99%
“…This type of response has been shown to be associated with the elimination of M. tuberculosis infection and suggests that such patients may not require prophylactic therapy [10,27,32].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…16e22 Other studies have shown that IFN-g alone is not sufficient to provide protection against disease progression 23 and that tumor necrosis factor (TNF)-a also is important in controlling MTB infection. 24 In addition, IL-2 was shown to correlate with pathogen load, 25 and IL-4 and IL-10 levels also were linked closely to active TB. 26 In particular, CXCL9 [also known as monokine induced by IFN-g (MIG)], was increased in plasma in patients with active PTB and tuberculous pleurisy compared with healthy controls, and secretion of IL-2, CXCL10 [IFN-g inducible protein 10 (IP-10)], and CXCL11 [IFN-inducible T-cell a chemoattractant (I-TAC)] was enhanced in LTBI individuals.…”
mentioning
confidence: 94%